Transcriptome and Metabolome Analyses Reveal the Regulatory Mechanism of TC1a in the Sucrose and Starch Synthesis Pathways in Arabidopsis thaliana - Wenjun Zhu; Guangze Li; Han Shi; Ying Ruan; Chunlin Liu (Plants)
Tumor necrosis factor receptor-associated factor (TRAF) proteins, originally identified in mammals, have since been found in most plants. TRAF proteins in plants have been shown to be involved in cellular autophagy, immunity, drought resistance, and ABA induction. However, the role in regulating sucrose and starch metabolism has not been reported. In this study, we confirmed that TC1a can regulate sucrose and starch metabolism through gene editing, phenotypic observation, transcriptomics and metabolomics analyses. Initially, 200 and 81 TRAF proteins were identified in rapeseed (Brassica napus L.) and Arabidopsis thaliana, respectively, and divided into five classes. We found that overexpression of TC1a inhibited root length, plant height, flowering, and leaf development in A. thaliana. Additionally, 12 differentially expressed genes (DEGs) related to sucrose and starch metabolism pathways were identified in overexpressing and knockout plants, respectively. Six differentially accumulated metabolites (DAMs)—fructose, sucrose, glucose, trehalose, maltose, and 6-phosphate fructose—were identified using widely targeted metabolomics analysis. The results show that TC1a affects the growth and development of Arabidopsis, and induces the expression of sucrose and starch synthase and hydrolases, providing a foundation for further research into its molecular mechanisms.